Pengaruh Pendidikan Kewirausahaan dan Motivasi Berwirausaha Terhadap Minat Berwirausaha dengan Self-Efficacy sebagai Variabel Intervening: Studi pada Siswa SMK Darut Taqwa Sengonagung Purwosari Pasuruan - Maslikhatul Uriva Chuswanto; Nur Rohmad Nuzil (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The author's background is the level of interest in entrepreneurship as seen throughentrepreneurship education, entrepreneurship motivation and self-efficacy, all of whichhave not been categorized as good and meet the entrepreneurship interests of students atDarut Taqwa Sengonagung Vocational School. The formulation of the problem in thisresearch is how entrepreneurship education, entrepreneurial motivation influencesinterest in entrepreneurship through self-efficacy in Darut Taqwa SengonagungVocational School students.The aim of this research is to determine and analyze entrepreneurial educationvariables, entrepreneurial motivation which influences interest in entrepreneurshipthrough self-efficacy in Darut Taqwa Sengonagung Vocational School students.This research was conducted to determine